The Illocutionary Acts in Sonic, The Hedgehog Movie - Ni Wayan Suastini; Ni Nyoman Deni Ariyaningsih; Ni Wayan Dita Novita Sari (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Abstrak This study focused on analyzing the types of illocutionary acts and the implied meaning of illocutionary act found in the characters utterance in Sonic, The Hedgehog movie. This study used the theory proposed by Searle (1979), about the types of illocutionary acts and a theory from Leech (1981), about the meaning. The data were collected by using library research. The method of analyzing the data was descriptive qualitative method. Formal and informal method is used to present the finding. The finding of this study shows that there are 35 data of illocutionary acts found in Sonic, The Hedgehog movie. Those five types of illocutionary acts consist of 10 ( 29%) data of representatives, 14 (40%) data of directives, 5 (14%) of commissives, 5 (14%) data of expressives and 1 (3%) datum of declaratives. Keywords: Illocutionary acts, implied meaning Abstrak Penelitian ini difokuskan untuk menganalisis jenis-jenis tindak tindak ilokusi dan makna tersirat dari tindak ilokusi tersebut yang terkandung di dalam pesan karakter dalam film Sonic, The Hedgehog. Penelitian ini menggunakan teori yang dikemukakan oleh Searle (1979), tentang jenis-jenis tindakan ilokusi dan teori dari Leech (1981), tentang makna. Pengumpulan data dilakukan dengan studi pustaka. Data di analisis menggunakan metode deskriptif kualitatif. Metode formal dan informal digunakan untuk menyajikan temuan. Hasil penelitian menunjukkan bahwa terdapat 35 data dari tindak ilokusi yang ditemukan dalam film Sonic, The Hedgehog. Kelima jenis ilokusi tersebut terdiri dari 10 (29%) data representatif, 14 (40%) data direktif, 5 (14%) data komisif, 5 (14%) data ekspresif dan 1 (3%) data deklaratif. Kata kunci : Tindakan ilokusi, makna tersirat